Life Cycle of Hammondia hammondi (Apicomplexa: Sarcocystidae) in Cats. (10th November 2014) - Dubey, Jitender P.; Ferguson, David J. P.
ABSTRACT: Hammondia hammondi and Toxoplasma gondii are feline coccidians that are morphologically, antigenically, and phylogenitically related. Both parasites multiply asexually and sexually in feline intestinal enterocytes, but H. hammondi remains confined to enterocytes whereas T. gondii also parasitizes extra‐intestinal tissues of the cat. Here, we studied multiplication of H. hammondi in feline intestine and compared with T. gondii cycle. Five parasite–free cats were inoculated orally with tissue cysts and free bradyzoites from skeletal muscles of gamma interferon gene knockout mice and killed at 1, 3, 4, 6, and 7 d later. At 1 and 3 d post inoculation (DPI), numerous individual intracellular bradyzoites were detected in histological sections of small intestine. At 4 DPI only schizonts were found and they were located in enterocyte cytoplasm above the host cell nucleus. At 6 and 7 DPI both schizonts and gamonts were seen and they were located in enterocytes. Ultrastucturally, schizogonic and gametogonic development of H. hammondi was similar to T. gondii . However, in H. hammondi merozoites rhoptries were longer, and coiled and contained more micronemes than in T. gondii . Ultrastructural development is illustrated in detail.